Student Centered Learning in Arabic Language Education: Integrating Research, Community Engagement, and Microteaching - Rojja Pebrian; Saproni Muhammad Samin (ALSINATUNA, 2026)
This evaluation looks at how Student‑Centered Learning (SCL) actually works in an Arabic Language Education program, and what it seems to be achieving. We used a Goal‑Free Evaluation Model (GFEM) within a convergent mixed‑methods design, drawing on Outcome‑Based Education documents (Graduate Learning Outcomes/GLO, Course Learning Outcomes/CLO, and syllabi), Learning Management System (LMS) records, micro‑teaching instruments, publication and Community Engagement (CE) portfolios, Quality Assurance reports, administrative data, and interviews and focus‑group discussions (FGDs) with stakeholders; the core indicators were also checked against the program's external accreditation field assessment. SCL is not a one‑off effort here but a routine part of how the program runs: tasks are managed through the LMS with standardized rubrics, more than 30 courses weave research and community engagement into coursework, and micro‑teaching gives every student at least four practice sessions, ten or more core skills, and structured cycles of feedback and reflection. Most indicators look encouraging a mean GPA of 3.7, tracer coverage of 92.86%, an employability/entrepreneurship/further‑study rate of 97.5%, field of work suitability of 95.0%, and an average job‑waiting time of 4.7 months though the average time‑to‑degree of 4.2 years and an on‑time graduation rate of just 37.2% stand out as clear weak points and a priority for improvement. Because the design is descriptive and goal‑free, we report associations rather than proven causes: three mechanisms plausibly help explain the link between SCL and these outcomes clearer alignment from GLO to CLO to assessment, dense practice with timely feedback, and authentic tasks grounded in real contexts. Going forward, the program should sharpen course‑level targets, calibrate rubrics more consistently, standardize how research and CE are built into courses, and strengthen career and thesis supervision support. Overall, these routines offer a workable, identity‑rooted blueprint that other programs could adapt.